1996
DOI: 10.1080/10826069608000049
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Rat Liver Mevalonate Pyrophosphate Decarboxylase

Abstract: Mevalonate pyrophosphate decarboxylase was isolated from rat liver to 90% purity as judged by SDS-PAGE using Phenyl Sepharose, p-coumaric acid-Sepharose, Mono P, and Mono Q chromatography. Gel filtration chromatography of the crude extract determined the native enzyme to be near 100 kDa while SDS-PAGE of the purified enzyme showed a protein band at 45 kDa. This implies that the native rat liver enzyme is a homodimer which differs from the published report that the enzyme is a tetramer of 35 kDa subunits. We me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
15
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 4 publications
3
15
0
Order By: Relevance
“…Shama Bhat and Ramasarma reported that rat liver MPD was composed of four subunits of 35 kDa each and was unstable when stored at 4°C. 6) On the other hand, Toth et al 7) reported a homodimer of 45-kDa MPD subunits in rats that was stable at 4°C. It is likely that the activity remaining in the supernatant after immunoprecipitation with anti-rat MPD antibody-Affigel 10 or anti-rat MPD antibody-protein A is from an unstable form of the enzyme like the rat MPD reported by Shama Bhat and Ramasarma.…”
Section: Fig 1(d) Isoelectric Points Of Mpdmentioning
confidence: 99%
See 2 more Smart Citations
“…Shama Bhat and Ramasarma reported that rat liver MPD was composed of four subunits of 35 kDa each and was unstable when stored at 4°C. 6) On the other hand, Toth et al 7) reported a homodimer of 45-kDa MPD subunits in rats that was stable at 4°C. It is likely that the activity remaining in the supernatant after immunoprecipitation with anti-rat MPD antibody-Affigel 10 or anti-rat MPD antibody-protein A is from an unstable form of the enzyme like the rat MPD reported by Shama Bhat and Ramasarma.…”
Section: Fig 1(d) Isoelectric Points Of Mpdmentioning
confidence: 99%
“…MPD has been purifed from various sources including yeast, 1,2) latex of Hevea brasiliensis, 3) pig liver, 4,5) rat liver, [6][7][8] and chicken liver. 9) Its properties in rat and chicken have been examined in detail.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This decarboxylase catalyzes a bimolecular reaction between mevalonate pyrophosphate and adenosine 5Ј-triphosphate (ATP) to form isopentenyl pyrophosphate, inorganic phosphate, ATP, and CO 2 . The enzyme has been purified from various sources, including yeast, 1,2) latex of Hevea brasiliensis, 3) pig liver, 4,5) rat liver, [6][7][8] and chicken liver. 9) Toth and Huwyler reported the cDNA sequences of MPD from human liver and yeast.…”
mentioning
confidence: 99%
“…[6][7][8] The cDNA sequences of 45-kDa MPD from rats were described by gene bank. We have purified and characterized 45-kDa MPD from rat liver and polyclonal antiserum raised against 45-kDa MPD.…”
mentioning
confidence: 99%